2018
DOI: 10.1016/j.jpain.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Children With Chronic Pain: Response Trajectories After Intensive Pain Rehabilitation Treatment

Abstract: Deriving groups of individuals with differing treatment response trajectories stimulates new thinking regarding potential mechanisms that may be driving these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 35 publications
(44 reference statements)
1
94
3
Order By: Relevance
“…In addition, it should be further considered whether a linear trend is the best method to interpret response to chronic pain rehabilitation. Simons and colleagues recently identified potentially different trajectories in response to chronic pain rehabilitation, such as early and late responders . Although our data supported a significant linear trend, as this research field develops, there may be compelling reasons to examine other response trajectories, as well as factors that predict the response.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In addition, it should be further considered whether a linear trend is the best method to interpret response to chronic pain rehabilitation. Simons and colleagues recently identified potentially different trajectories in response to chronic pain rehabilitation, such as early and late responders . Although our data supported a significant linear trend, as this research field develops, there may be compelling reasons to examine other response trajectories, as well as factors that predict the response.…”
Section: Discussioncontrasting
confidence: 49%
“…Our study also provides initial data to support the hypothesized model that, for pediatric chronic pain, treatment should target independent functioning as a primary outcome, and patients should not anticipate a reduction in pain until at a later phase of rehabilitation. Interestingly, though not unexpected, pain level was significantly lower yet not eliminated over a 1‐year time period (Table , Figure ). The majority of our patients still reported pain from headache 1 year following rehabilitation.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous study based on a large group of patients (n = 253) suggested the predictive influence of several baseline characteristics (e.g. pain problem complexity, older adolescence age and cognitive-affective factors) [55]. However, results from this work showed that brain metric measures might have a better performance in the prediction of individual responsivity, especially when only limited prior information is available.…”
Section: Discussionmentioning
confidence: 81%
“…One of the observations in the latter reports was the ‘normalization’ of networks and gray matter changes when pretreatment vs. posttreament scans were evaluated. Despite observed changes in brain metrics and converging evidence of improved pain and functioning [26; 33; 56], not all patients respond to treatment with improvements in pain [55]. Despite emerging evidence of brain markers of the transition from acute to chronic pain [4; 25], there is no known data on baseline brain metrics that can distinguish pain responders and nonresponders who undergo pain treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of these states of decreasing the threshold for activation of pain awareness have not been explored. However, associated symptoms such as catastrophizing (Coronado et al, 2015; Quartana et al, 2009) or fear of pain (Simons et al, 2012, 2017) may predict later onset of pain. Some have argued that anxiety or chronic stress may exacerbate pain (Li et al, 2017) through alteration in specific nuclei (e.g., amygdala) via a process that induced neuronal sensitization due to decreased inhibition (Jiang et al, 2014).…”
Section: When Pain Pops Out To Conscious Awareness – Insights Frommentioning
confidence: 99%